The Impact of Tourism Investment on Employment in the Sultanate of Oman: A Statistical Analysis (2018–2023) - Haidar, Al Ajmi Zamzam Yousuf; Hassan, Wan Zulkifli Wan (Journal of Ecohumanism, 2025)
This study investigates the impact of tourism investment on employment in the Sultanate of Oman during the period 2018–2023. Drawing on data from the Tourism Statistics Bulletin 2023 issued by the National Center for Statistics and Information, the research analyzes the relationship between tourism infrastructure growth and job creation in both direct and indirect sectors. The findings indicate that tourism investments, particularly in hotel development, led to a 20.6% increase in the number of hotels, totaling 813 hotels in 2023, and a 7.7% rise in employment, with the workforce reaching 21,984 in 2023. However, the sector continues to face challenges, including a high reliance on expatriate workers (67.6%) and an unequal concentration of investments in urban centers like Muscat (28% of hotels). Tourism revenues also showed significant growth, with inbound tourism generating OMR 826 million and domestic tourism contributing OMR 829 million in 2023. The study highlights the importance of addressing these challenges through targeted strategies, such as promoting rural tourism, enhancing Omanization through vocational training, and adopting sustainable tourism practices. These measures are essential to ensuring long-term growth, reducing regional disparities, and aligning the tourism sector with Oman Vision 2040’s goals of economic diversification and social inclusion.